The Monastery of Val de Cristo in the Kingdom of Valencia: Relations, Economy, and Significance to the Crown 1410–50 - Webster, Jill R. (Journal of Medieval Monastic Studies, 2012)
Abstract The charterhouse of Val de Cristo near Segovia played an important role in the lives of King Martin and his queen and was closely allied with the monastic house of Portacoeli. The lands, benefices, and rights the two monasteries held in Castellón were the cause of a long dispute held between them and the diocese of Tortosa, which contended that the Castellón lands fell within its jurisdiction. The present article focuses on the way this contentious issue was resolved in the mid-fifteenth century and is supported by a documentary appendix outlining the process that led to the final decision almost fifty years later.